Transnational Islamic Movement: The Da’wah Movement of Salafism in Southeast Sulawesi - Muhammad Alifuddin; Iye, Risman; Rusnam; Fithriyah Inda Nur Abida (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2024)
This article reports on research conducted through observations, document studies, and in-depth interviews, with several Salafi activists in Southest Sulawesi regarding the strategy of da’wah movement. Using a phenomenological hermeneutic approach, this study has revealed that the traces of salafism in Southeast Sulawesi began in 1998 when a number of Middle Eastern alumni from this area returned and became agents of spreading the idea of salafism in Southeast Sulawesi. Furthermore, the growth of Salafi communities is attributed to effective institutional management, particularly their ability to mobilize da’wah resources and establish communication with external parties. However, other Salafi communities tend to remain rigid, prioritizing stability and consistency in adhering to the manhaj sunnah.